Changes in the structure of sandy and silty sediments after 1000 freeze-thaw cycles – preliminary results from laboratory experiment - Śniady, Igor (Acta Geographica Lodziensia, 2024)
The laboratory experiment included analysis of the changes in sediment structure resulting from the reorganization of sediment grains subjected to repeated freeze-thaw cycles. A freeze-thaw device operating in temperatures ranging from ˗5°C to +10 °C was used for this purpose. In five transparent plexiglass cylinders were placed, in order from bottom to top, the following sediments: coarse sand, fine sand, silt and again fine sand. The degree of sediment hydration differed for each of the cylinders. Observations of changes were made macroscopically on the basis of photographic documentation of the cylinders taken before the start of the experiment and after 250, 500, 750 and 1000 cycles of freezing and thawing. The highest grain reorganization was found for silty sediment and the lowest for coarse sand. In addition, the reorganization of grains was significantly affected by the sample hydration. The highest number of structures was formed at the boundaries between fine sand and silt in the cylinders with the highest hydration.